2013
DOI: 10.1002/glia.22489
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming neurite‐inhibitory chondroitin sulfate proteoglycans in the astrocyte matrix

Abstract: Acute trauma to the central nervous system (CNS) can result in permanent damage and loss of function related to the poor regeneration of injured axons. Injured axons encounter several barriers to regeneration, such as the glial scar at the injury site. The glial scar contains extracellular matrix (ECM) macromolecules deposited by reactive astrocytes in response to injury. The scar ECM is rich in chondroitin sulfate proteoglycans (CSPGs), macromolecules that inhibit axonal growth. CSPGs consist of a core protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 77 publications
2
57
0
Order By: Relevance
“…In studies, CSPGs degradation by ADAMT4 showed that ADAMTS4 overcomes inhibition of axonal regeneration and promotes neurite outgrowth through a proteolytic mechanism [43]. ADAMTS4 caused a decrease in phosphocan accumulation [44], and ADAMTS4 increased the neurite outgrowth on rat neuron culture [45].…”
Section: Biochemical Enzymatic Degradations In Extracellular Space Thmentioning
confidence: 99%
“…In studies, CSPGs degradation by ADAMT4 showed that ADAMTS4 overcomes inhibition of axonal regeneration and promotes neurite outgrowth through a proteolytic mechanism [43]. ADAMTS4 caused a decrease in phosphocan accumulation [44], and ADAMTS4 increased the neurite outgrowth on rat neuron culture [45].…”
Section: Biochemical Enzymatic Degradations In Extracellular Space Thmentioning
confidence: 99%
“…Degradation of CSPG core proteins by matrix metalloproteinases, including a disintegrin and metalloproteinase with thrombospondin motifs 4 (ADAMTS-4), overcomes CSPG inhibition on neurite growth in culture (Cua et al, 2013). Local administration of ADAMTS-4 enhanced axonal regeneration/sprouting and promoted motor function recovery after SCI (Tauchi et al, 2012).…”
Section: Functions Of Reactive Scar Tissue After Cns Injurymentioning
confidence: 99%
“…Cua and collaborators (2013) reported that ADAMTS-4 was more efficient at degrading CSPGs and inducing subsequent neurite growth in vitro than chondroitinase ABC or MMPs [58]. …”
Section: Introductionmentioning
confidence: 99%